Social Movements : the Key Concepts. - Chesters, Graeme (Routledge key guides., 2010)
"Social Movements: The key Concepts" has relevance for a range of disciplines such as healthcare, development studies, anthropology and globalization. Material covered includes the Civil Rights Movement, direct action, hactyvism, indymedia, feminism and the Anti-Globalization Movement. An A-Z Index and extensive bibliography provides tips for further exploration of this fascinating field. Students of all levels stand to gain much from this up-to-date and compact distillation of all the key facts.